Neural Correlates of Stress and Abdominal Obesity in Patients With Coronary Artery Disease. Issue 3 (April 2020) - Moazzami, Kasra; Wittbrodt, Matthew T.; Lima, Bruno B.; Levantsevych, Oleksiy; Kaseer, Belal; Martini, Afif; Haffar, Ammer; Nye, Jonathon A.; Quyyumi, Arshed A.; Shah, Amit; Vaccarino, Viola; Bremner, J. Douglas
ABSTRACT: Objective: This study aimed to investigate the relationship between waist circumference as a measure of abdominal obesity and brain responses to stress among patients with coronary artery disease (CAD). Methods: Patients with CAD ( N = 151) underwent acute mental stress tasks in conjunction with high-resolution positron emission tomography and radiolabeled water imaging of the brain. Brain responses to mental stress were correlated with waist circumference. Results: Waist circumference was positively correlated with increased activation in the right and left frontal lobes (β values ranging from 2.81 to 3.75 in the paracentral, medial, and superior gyri), left temporal lobe, left hippocampal, left amygdala, left uncus, and left anterior and posterior cingulate gyri (β values ranging from 2.93 to 3.55). Waist circumference was also negatively associated with the left and right parietal lobes, right superior temporal gyrus, and right insula and precuneus (β values ranging from 2.82 to 5.20). Conclusion: Increased brain activation in the brain regions involved in the stress response and autonomic regulation of the cardiovascular system during psychological stress may underlie stress-induced overeating and abdominal obesity in patients with CAD.